L'implementazione tecnica della Direttiva Inspire e del suo recepimento nazionale: l'approccio broker per la condivisione dei metadati - Bonora, Nico; Boldrini, Enrico; Munafò, Michele; Nativi, Stefano (GEOmedia, 2013)
La Direttiva 2007/2/CE del Parlamento Europeo e del Consiglio del 14 marzo 2007, che istituisce un'Infrastruttura per l'informazione territoriale nella Comunità europea (Inspire), impone agli stati membri di fornire gli elementi conoscitivi ed informativi relativi ai dati ambientali prodotti a scala nazionale. The brokering approach to support the implementation of INSPIRE in Italy. The National implementation of the INSPIRE Directive (Italian Legislative Decree 32/2010) identifies ISPRA as the authority in charge to progressively integrate environmental datasets in the frame of the Italian Environmental Information System (developed by ISPRA) and through its Network, and Public (Regional) Authorities are asked to make available to ISPRA the informative elements (metadata) to ensure interoperability of environmental datasets and associated services. With the aim to fulfill what stated above, ISPRA, in collaboration with CNR, implemented a network of metadata catalogs on the basis of the System of Systems model. Remote (Regional) resources are accessed by a broker Catalog capable to expose and recognize different standard interfaces and metadata models. Today, the network collects more than 12000 metadata and services.